2013
DOI: 10.1073/pnas.1312857110
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin enhances brain function in children with autism

Abstract: Following intranasal administration of oxytocin (OT), we measured, via functional MRI, changes in brain activity during judgments of socially (Eyes) and nonsocially (Vehicles) meaningful pictures in 17 children with high-functioning autism spectrum disorder (ASD). OT increased activity in the striatum, the middle frontal gyrus, the medial prefrontal cortex, the right orbitofrontal cortex, and the left superior temporal sulcus. In the striatum, nucleus accumbens, left posterior superior temporal sulcus, and lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
220
3
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(266 citation statements)
references
References 71 publications
(81 reference statements)
17
220
3
6
Order By: Relevance
“…In contrast, the STS, which activated all fathers' responses to infant cues, had both a direct effect on synchrony and mediated effects via oxytocin, which has been repeatedly shown to support the development of synchronous parenting (5,20,21). Oxytocin administration has been shown to increase STS response to tasks that require mentalizing (36). Thus, our model charts two pathways of brain-hormonebehavior in first-time parents: one mediated by the amygdala for mothers and the other by the STS for fathers.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the STS, which activated all fathers' responses to infant cues, had both a direct effect on synchrony and mediated effects via oxytocin, which has been repeatedly shown to support the development of synchronous parenting (5,20,21). Oxytocin administration has been shown to increase STS response to tasks that require mentalizing (36). Thus, our model charts two pathways of brain-hormonebehavior in first-time parents: one mediated by the amygdala for mothers and the other by the STS for fathers.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, exogenous OXT can restore various aspects of social behaviour and cognitive dysfunction associated with neuropsychiatric disorders including autism spectrum disorders (ASDs) (Gordon et al . 2013; Peñagarikano et al . 2015).…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 99%
“…Oxytocin is synthesized in the hypothalamus and projects from the hypothalamus to the amygdala, striatum, suprachiasmatic nucleus, and brainstem (Ludwig and Leng, 2006;Donaldson and Young, 2008). Intranasal administration of oxytocin has been shown to mainly modulate neural activity in the amygdala (Domes et al, 2007;Petrovic et al, 2008;Baumgartner et al, 2008), midbrain/striatum/NAcc (Baumgartner et al, 2008;Gordon et al, 2013;Groppe et al, 2013), mPFC (Petrovic et al, 2008;Gordon et al, 2013), and OFC (Petrovic et al, 2008;Gordon et al, 2013). These findings suggested that the oxytocinergic system and the intuition system involved common neural underpinnings.…”
Section: Introductionmentioning
confidence: 99%